2021
DOI: 10.1186/s12889-021-11672-1
|View full text |Cite
|
Sign up to set email alerts
|

Young migrants’ sexual rights in Sweden: a cross-sectional study

Abstract: Background In national public health surveys including those assessing sexual and reproductive health, migrants generally tend to be underrepresented due to cultural, linguistic, structural and legal barriers, minimising the possibility to measure sexual rights’ fulfilment in this group. This study aims to describe to what extent sexual rights of young migrants in Sweden are being fulfilled. Methods A self-administered questionnaire was used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 21 publications
0
27
0
3
Order By: Relevance
“…This means that the experiences of any young migrants not falling into one of these four categories are largely missing from academic discourse. This is supported by the single study that looked at migrants more broadly [ 19 ], which included all migrants regardless of their reason for migrating or their legal status. This study found that vulnerabilities to sexual violence varied by sexual orientation and gender identity, legal status and region of origin [ 19 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This means that the experiences of any young migrants not falling into one of these four categories are largely missing from academic discourse. This is supported by the single study that looked at migrants more broadly [ 19 ], which included all migrants regardless of their reason for migrating or their legal status. This study found that vulnerabilities to sexual violence varied by sexual orientation and gender identity, legal status and region of origin [ 19 ].…”
Section: Resultsmentioning
confidence: 93%
“…One of the key issues with the quantitative studies included in this review was the sample sizes which varied widely between 1773 [ 19 ] and 19 [ 20 ] (see Table 3 for details). Small sample sizes may be a direct consequence of investigating very specific populations in a particular context but can limit the generalisability of the data collected.…”
Section: Resultsmentioning
confidence: 99%
“…MRY's ignorance of SRH services is consistent with comparable studies in other high-income countries. 70 Youth's misgivings about health and legal support overwhelmingly related to social risk; fears of negative repercussions for seeking support and that doctors would breach confidentiality. Mistrust indicates services have not effectively engaged MRY or presented themselves as safe spaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are indications that migrant men in Sweden face more difficulties accessing and might have worse experiences receiving SRH services compared to migrant women. ( Baroudi et al., 2021 ; Baroudi et al., 2022 ). Previous research showed that fewer migrant men visited SRH services (9.4% vs. 22.2% of women), and, adjusted for needs, only 23% of migrant men had their needs fulfilled by SRH services compared to 52% of migrant women ( Baroudi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that fewer migrant men visited SRH services (9.4% vs. 22.2% of women), and, adjusted for needs, only 23% of migrant men had their needs fulfilled by SRH services compared to 52% of migrant women ( Baroudi et al., 2022 ). Additionally, compared to migrant women, more migrant men reported; feeling disrespected during a visit to SRH services (9.1% vs. 6.9% of women); perceiving discrimination (13.1% vs. 9.7% of women); perceiving a prejudiced attitude of the staff toward them (32.9% vs. 24.8% of women); and not receiving the expected help (30.1% vs. 20.2% of women) ( Baroudi et al., 2021 ). Worse experiences in SRH services among migrant men are also reported in other studies from the European Union ( Cha, 2013 ; Lebano et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%